ҚОРАҚАЛПОҒИСТОННИНГ БИР ЙИЛЛИК ГАЛОФИТЛАРИ: БИОЛОГИК ХУСУСИЯТЛАРИ ВА ЭКОЛОГИК АҲАМИЯТИ - Сабиров, Д.Г.; Ешмуратов, Р.А. (SCIENCE and SOCIETY, 2025)
The article discusses the importance of annual halophytic plants in the territory of Karakalpakstan. It is noted that the propagation of annual halophytes is one of the main ways to improve the unfavorable environmental conditions. The article provides information on the influence of air temperature, water and salt content in the soil on these plants, their biological characteristics, and vegetation periods.
Keywords: halophyte; plant; annual; Karakalpakstan; saline; soil; desert; family; genus; species; growth; salt; island; saltworts